Educación ambiental como estrategia para el manejo de residuos sólidos de las actividades turísticas en la represa La Esperanza, Bolívar, Manabí - Mendoza López, Yosselyn Ambar (2021)
The objective of this research was to establish an environmental education program for the management of solid waste generated by tourism activities at La Esperanza dam. A diagnosis was made using a hierarchical ranking of tourist attractions, where it was determined that there are 20 tourist attractions in La Esperanza dam, of which 13 local entrepreneurs are currently working. Through an observation sheet, 14 types of waste were identified; by means of the percentage composition of solid waste, 55.78% of organic waste was registered, followed by glass (32.7%) and plastic waste (7.03%), originating a total of 542.34 kg produced per 8 weeks, registering a per capita production of 0.34 kg/tourists/week, by the selective collection method. In order to determine the environmental knowledge, an evaluation scale was used, through the use of a questionnaire, where it was evidenced in the initial evaluation 30.15% (4) obtained a Good level of knowledge (11 - 15); 53.85% (7) obtained a Regular level (6 - 10); while the deficient level (1 - 5), was 15, 38% (2) on the part of the participants. With the environmental education strategy for the adequate management of solid waste, there was an increase in the level of knowledge reaching 92.31%, considered good, demonstrating that the E.A. program had a positive influence on the knowledge of the participants, thus guaranteeing an adequate management of solid waste.